2020
DOI: 10.1002/mas.21669
|View full text |Cite
|
Sign up to set email alerts
|

Laser Ionization Mass Spectrometry at 55: Quo Vadis?

Abstract: Laser ionization mass spectrometry (LIMS) was one of the first practical methods developed for in situ analysis of the surfaces of solid samples. This review will encompass several aspects related to this analytical method. First, we will discuss the process of laser ionization, the influence of the laser type on its performance, and imaging capabilities of this method. In the second chapter, we will follow the historic development of LIMS instrumentation. After a brief overview of the first-generation instrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 265 publications
0
23
0
Order By: Relevance
“…The historic development of LIMS instrumentation is well-documented in a recent review and includes a brief overview of the first-generation instruments and more recent designs developed between 1960 and 1990 [1]. The limited number of femtosecond-LIMS instruments so far is a result of the high price of the fs-laser system and perhaps of the prevailing experience from the nanosecond predecessor of this method about the qualitative rather than quantitative capabilities of LIMS.…”
Section: Selected Femtosecond-lims Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…The historic development of LIMS instrumentation is well-documented in a recent review and includes a brief overview of the first-generation instruments and more recent designs developed between 1960 and 1990 [1]. The limited number of femtosecond-LIMS instruments so far is a result of the high price of the fs-laser system and perhaps of the prevailing experience from the nanosecond predecessor of this method about the qualitative rather than quantitative capabilities of LIMS.…”
Section: Selected Femtosecond-lims Systemsmentioning
confidence: 99%
“…LIMS has a rich history spanning more than 50 years. The initial fast expansion lasted from the middle of the 1970s to the beginning of the 1990s, when it offered the most affordable and fast method of analysing solid samples, including organic and bioorganic compounds [1][2][3]. Several commercial instruments such as LAMMA-500, -1000, -2000 became available in the 1970s [2,[4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,5 Recently, we have shown that an extreme ultraviolet (EUV) laser coupled to a mass spectrometer can also offer unsurpassed three-dimensional (3D) nanoscale spatial resolution for chemical mapping. [12][13][14][15] Our group at Colorado State University (CSU) has built and developed an EUV laser ablation and ionization time-offlight mass spectrometer (EUV TOF) that was the first of its kind to achieve mass spectral imaging with 3D nanoscale spatial resolution. 12,13 The instrument uses a table-top EUV Ar 8+ capillary discharge laser, also developed at CSU, that operates at a wavelength of 46.9 nm (26.4 eV photon energy).…”
Section: Introductionmentioning
confidence: 99%